Zagadnienie stosowania przepisów kodeksu cywilnego do określenia niektórych następstw relacji płatnik–ubezpieczony z punktu widzenia założenia racjonalności prawodawcy - Babińska-Górecka, Renata (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The article analyses the problem of admissibility and legal grounds for the payer to claim from the insured the return of a part of the premium paid from the payer’s own resources, which according to the Act is financed by the insured. The study attempts to assess whether there is a gap in social insurance law in this case, or whether it can be based on another basis — by applying the provisions of the Civil Code on unjust enrichment or third party performance — to formulate an appropriate recourse claim of the contribution payer against the insured. Assumptions about the legislator’s linguistic and axiological rationality were made as a reference point for the considerations and interpretations of legal provisions.
Keywords: contribution payer; insured; civil law; social insurance law; assumption of the legislator’s rationality